Agility sustainable supply chain in automobile industry - Bathaei, Ahmad; Awang, Siti Rahmah; Štreimikienė, Dalia; Ahmad, Tahir (Technological and Economic Development of Economy, 2025)
Automobile industries are facing rapid and unanticipated changes in their business environment. New strategies are needed to remain competitive in the market for those companies. The supply chain plays a crucial role in automobile companies, and improving the supply chain helps them to be successful in the competition. The agile paradigm allows companies to be flexible in the competition, and also sustainable paradigm helps them to popularity among the organizational system. The primary purpose of this study is to combine agile supply chain and sustainable supply chain as one strategy. For this purpose, 73 factors obtained from previous studies and the Fuzzy Delphi Method and Fuzzy Best Worst Method were used to find the best factors and rank them. The results show that 26 elements accepted and after ranking Quality, Supply chain configuration, Customer satisfaction, Suppliers ’green initiatives and Top management vision were the best five factors. In addition, the results confirmed the finding and the new model for an agile sustainable supply chain.